2021
DOI: 10.3390/app112411852
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Estimation of Earthquake Magnitude and Source Parameters Using Genetic Algorithms

Abstract: To minimize the impacts of large losses and optimize the emergency response when a large earthquake occurs, an accurate early warning of an earthquake or tsunami is crucial. One important parameter that can provide an accurate early warning is the earthquake’s magnitude. This study proposes a method for estimating the magnitude, and some of the source parameters, of an earthquake using genetic algorithms (GAs). In this study, GAs were used to perform an inversion of Okada’s model from earthquake displacement d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Traditional methods based on seismometer data are inaccurate in such short period of time, and they tend to underestimate the value of the magnitude in large earthquakes (Novianty et al, 2021). Blewitt et al (2006) demonstrated that the earthquake magnitude can be determined using high-resolution GPS data within the first 15 min after the start of the earthquake, by tracking the mean displacement of the Earth's surface associated with the arrival of seismic waves.…”
Section: Estimation Of the Magnitude M Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional methods based on seismometer data are inaccurate in such short period of time, and they tend to underestimate the value of the magnitude in large earthquakes (Novianty et al, 2021). Blewitt et al (2006) demonstrated that the earthquake magnitude can be determined using high-resolution GPS data within the first 15 min after the start of the earthquake, by tracking the mean displacement of the Earth's surface associated with the arrival of seismic waves.…”
Section: Estimation Of the Magnitude M Wmentioning
confidence: 99%
“…In order to apply scaling laws when an earthquake has been detected, previously its magnitude M w should be determined as fast an accurately as possible, ideally within a few minutes after the occurrence of the earthquake. Traditional methods based on seismometer data are inaccurate in such short period of time, and they tend to underestimate the value of the magnitude in large earthquakes (Novianty et al., 2021).…”
Section: Tsunami Generation Modelmentioning
confidence: 99%